Ex situ potential conservation of ipecacuanha (Psychotria ipecacuanha (Brot.) Stokes.), a critically endangered medicinal plant species (2017)
Psychotria ipecacuanha is a medicinal plant endangered in Colombia, due to the indiscriminate exploitation suffered several decades ago for its therapeutic importance. Its great medicinal value is due to emetine production and its derivatives, mainly in the roots. Given these concerns, the aim of this research was to evaluate different parameters for in vitro conservation of P. ipecacuanha by a limited plant growth, using as in vitro explants plant nodes. Plant growth response to 18, 23 and 25°C with and without addition to MS basal culture medium 15 and 30 gL-1 of mannitol osmotic regulator was evaluated. Registration of plant survival data (%), plant height (cm), plant development of axillary shoots, number of leaves, callus formation and vigour of developed buds and was initially performed at 3 months and then every two months until 12 months. The explants conserved for 9 months in culture medium without mannitol osmotic regulator and temperature of 18°C, showed response after transferring and reculturing in recovery culture medium for 6-8 weeks, this process had not achieved any effect on plant growth and vigour in the recovery phase. In addition, the critical parameters in the acclimatization process were determined.